Youtube Youtube dan Hak Cipta : Legalitas Hak Moral dalam Cover Music Atas Hasil Karya Pemuda Merauke - Yosman Leonard Silubun; Marlyn Jane Alputila (Musamus University, 2021)
Abstract The speed of the development of internet technology is very fast, not in line with the development of law. In accordance with the motto in the Dutch language